2021
DOI: 10.1016/j.bmc.2021.116393
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral evaluation of hydroxyethylamine analogs: Inhibitors of SARS-CoV-2 main protease (3CLpro), a virtual screening and simulation approach

Abstract: The continued toll of COVID-19 has halted the smooth functioning of civilization on a global scale. With a limited understanding of all the essential components of viral machinery and the lack of structural information of this new virus, initial drug discovery efforts had limited success. The availability of high-resolution crystal structures of functionally essential SARS-CoV-2 proteins, including 3CLpro, supports the development of target-specific therapeutics. 3CLpro, the main protease responsible for the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…19 Recently, several HEA analogs have been reported as efficacious against the SARS-CoV-2 virus. 20–22 FDA-approved protease inhibitors of HIV 18 also support the importance of the HEA pharmacophore (Fig. 1).…”
Section: Introductionmentioning
confidence: 78%
“…19 Recently, several HEA analogs have been reported as efficacious against the SARS-CoV-2 virus. 20–22 FDA-approved protease inhibitors of HIV 18 also support the importance of the HEA pharmacophore (Fig. 1).…”
Section: Introductionmentioning
confidence: 78%
“…The compound ( XXV ) was synthesized by the authors and has been evaluated for biological efficacy against the virus in cell media and depicted excellent results with an IC 50 value of 4.973 μM. In another report, Gupta et al 67 followed a similar methodology and suggested the strong binding affinity of three HEA-based compounds against the main protease of SARS-CoV-2. The best result among these was displayed by compound XXVI , an IC 50 value of 6.38 μM.…”
Section: Biological Efficacy Of Peptide Based Compounds Synthesized S...mentioning
confidence: 99%
“…A continued effort is warranted to explore new key targets for effective drug development against SARS-CoV-2 and new variants [ 10 ]. Target-based drug development is the most rapid pipeline to deliver potent molecules even from weaker initial hits [ 11 ].…”
Section: Introductionmentioning
confidence: 99%